Gaya Kepemimpinan Transformasional dan Motivasi Terhadap Kinerja Karyawan: Peran Mediasi Kepuasan Kerja - Supriyadi; Suhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to test and analyze the influence of leadership style and motivation on performance with mediation of job satisfaction. The sample used in this study was 126 employees. Testing includes instrument testing, model testing, hypothesis testing and Sobel test. The results of the analysis show that leadership style has a positive and significant effect on job satisfaction and performance. Motivation has a positive and significant effect on job satisfaction and performance. Job satisfaction has a positive and significant effect on performance. Job satisfaction mediates leadership style and motivation on performance. This study has theoretical and practical implications.